Relation of Sociodemographics and Personal Hygiene on Different Childhood Dermatoses - Gauchan, E; Kumar, A; BK, G; Thapa, P; Pun, J (Kathmandu University Medical Journal, 2015)
Background Skin diseases in children contribute to significant morbidity and psychological distress. Infective dermatoses are one of the major dermatoses in children. Low socioeconomic status, overcrowding and poor personal hygiene has been linked to skin diseases.Objective To find out the prevalence of infectious skin disease in children, rate of transmissible skin disease and association of sociodemographic factors and personal hygiene on infective childhood dermatoses.Method This was a cross-sectional study conducted in the Pediatric and Dermatology Department, Manipal Teaching Hospital, Pokhara, Nepal. A total of 226 patients were examined over a period of one year. Relation of sociodemographics, crowding and personal hygiene on skin disease were assessed.Result The most common category was Infections and Infestations (51.3%) followed by Dermatitis (27.9%) . Transmissible skin disease was seen in 49.6%. Low socioeconomic status and overcrowding were associated with increased risk for infective dermatoses.Conclusion Skin disease in children constitutes a public health problem. Improving the socioeconomic status and personal hygiene can help to reduce the incidence of skin disease in children.Kathmandu University Medical Journal Vol.13(1) 2015; 29-33